A conifer Pagiophyllum yafraiensis sp. nov. from the Jurassic Khashm az Zarzur Formation, Yafran, Jebel Nefusa – Libya. - Muftah, Ahmed; El Zouki, Ashor (Libyan Journal of Science &Technology, 2022)
The Jurassic flora from the Khashm az Zarzur Formation in the vicinity of Yafran village in Jebel Nefusa, northwestern Libya was studied. Among which a new species of fossil conifer, Pagiophyllum yafraiensis sp. nov. was described and illustrated. This new species occurred in association with Piazopteris branerii, Brachyphyllum sp., Hirmerella sp., Otozamites sp., and Samaropsis sp. According to the stratigraphic position of the Khashm az Zarzur Formation dated as (Callovian-Oxfordian), however, a Late Jurassic (Bathonian-Tithonian) age has been assigned palynologically. The global paleogeographical distribution of the genus Pagiophyllum is also illustrated herein.